2006
DOI: 10.1164/rccm.200506-964oc
|View full text |Cite
|
Sign up to set email alerts
|

Modified Th2 Responses at High-Dose Exposures to Allergen

Abstract: High exposure to rats is associated with lower rates of specific IgE and symptoms but an increased frequency of high specific IgG and IgG(4) production. Specific IgG(4) produced together with specific IgE may reduce the risk of developing work-related chest symptoms compared with when specific IgE is produced alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
68
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 22 publications
9
68
0
1
Order By: Relevance
“…In a cross-sectional study of rat workers, the risk of IgE sensitization was attenuated among those who handled the greatest number of rats per day, but the prevalence of rat-specifi c IgG and IgG4 was highest among this group [35]. Those in this highest exposure group were also less likely to have rat-associated allergic symptoms than workers with lower rat exposure.…”
Section: Ige Sensitizationmentioning
confidence: 98%
“…In a cross-sectional study of rat workers, the risk of IgE sensitization was attenuated among those who handled the greatest number of rats per day, but the prevalence of rat-specifi c IgG and IgG4 was highest among this group [35]. Those in this highest exposure group were also less likely to have rat-associated allergic symptoms than workers with lower rat exposure.…”
Section: Ige Sensitizationmentioning
confidence: 98%
“…24,25 A recent report on serological responses to rat urinary allergens has confirmed that a ''modified T H 2 response'' can also occur among animal handlers. 26 The reason for calling the response to cat, dog, mouse, or rat allergens a ''modified T H 2 response'' is both that expression of IgG 4 is IL-4-dependent and that this response does not include evidence for a T H 1 response. [24][25][26][27] The reason for regarding it as a form of tolerance is that individuals who have allergen-specific IgG 4 antibody without IgE antibody do not experience symptoms.…”
Section: Immune Responses To Indoor Allergensmentioning
confidence: 99%
“…26 The reason for calling the response to cat, dog, mouse, or rat allergens a ''modified T H 2 response'' is both that expression of IgG 4 is IL-4-dependent and that this response does not include evidence for a T H 1 response. [24][25][26][27] The reason for regarding it as a form of tolerance is that individuals who have allergen-specific IgG 4 antibody without IgE antibody do not experience symptoms. The mechanisms by which high exposure to one type of allergen could give rise to tolerance are not clear.…”
Section: Immune Responses To Indoor Allergensmentioning
confidence: 99%
“…A window of allergen exposure causing eosinophilia was evident particularly for animals sensitized when young and challenged as adults. Such attenuation of the allergic response at higher allergen exposures has been noted in clinical studies of cat, dust mite, and lab animal allergic populations (Jeal et al, 2006) and has been described as a modified T H 2 response. It is associated with lower rates of specific IgE and an increased frequency of specific IgG production.…”
Section: Discussionmentioning
confidence: 77%